Women's experiences of perinatal depression: Symptoms, barriers and enablers to disclosure, and effects on daily life and interaction within the family. (September 2022) - Pinar, Semra; Bedford, Helen; Ersser, Steven; McMillan, Dean
Abstract: Objective: Nearly half of all cases of perinatal depression are not detected, despite routine appointments with healthcare professionals (HCP) during pregnancy and after childbirth. Early identification of perinatal depression is crucial to provide the required support and offer timely treatment. This study aimed to explore women's experiences of perinatal depression to help identification and management of perinatal depression by HCPs. Design: Theoretical perspective of symbolic interactionism and methodological design of ethnography was adopted. Face-to-face individual interviews were used. Thematic analysis was conducted to analyse interview data. Participants: Fifteen women who had experienced perinatal depression in the last five years were interviewed. Findings: Three themes were identified: 1) Getting closer to the perinatal depression; 2) Decision to disclose or hide real feelings; 3) Hidden face of perinatal depression. Key conclusions and implications for practice: Findings demonstrate the importance of HCPs' attitudes towards women, as if women perceive they being dismissed or neglected by HCPs, may have an impact on women refraining from disclosing their feelings.